Perspectives on linkage to care for patients diagnosed with HIV: A qualitative study at a rural health center in South Western Uganda. - Mark Opio; Florence Akello; Doreen Kagina Twongyeirwe; David Opio; Juliet Aceng; Jane Kasozi Namagga; Jerome Kahuma Kabakyenga (PLoS ONE, 2022)
Linkage to care for newly diagnosed human immunodeficiency virus (HIV) patients is important to ensure that patients have good access to care. However, there is little information about factors influencing linkage to care for HIV patients. We aimed to identify existing measures in place that promote linkage to care and to explore facilitators and barriers to linkage to care for clients diagnosed with HIV/acquired immune deficiency syndrome at a rural health center in Uganda. This descriptive qualitative study enrolled 33 purposively selected participants who included expert clients, linkage facilitators, heads of families with people living with HIV, and health workers. Data were collected using in-depth interviews that were audio-recorded, transcribed, and translated. The data were manually analyzed to generate themes. The following four themes were generated: 1) availability of services that include counseling, testing, treatment, follow-up, referral, outreach activities, and support systems. 2) Barriers to linkage to care were at the individual, health facility, and community levels. Individual-level barriers were socioeconomic status, high transport costs, fear of adverse drug effects, fear of broken relationships, and denial of positive results or treatment, while health facility barriers were reported to be long waiting time, negative staff attitude, and drug stock outs. Community barriers were mostly due to stigma experienced by HIV clients, resulting in discrimination by community members. 3) Facilitators to linkage to care were positive staff attitudes, access to information, fear of death, and support from others. 4) Suggestions for improving service delivery were shortening waiting time, integrating HIV services, increasing staff numbers, and intensifying outreaches. Our findings highlight the importance of stakeholder involvement in linkage to care. Access and linkage to care are positively and negatively influenced at the individual, community, and health facility levels. However, integration of HIV services and intensifying outreaches are key to improving linkage to care.